2005
DOI: 10.1242/jeb.01613
|View full text |Cite
|
Sign up to set email alerts
|

Do monarch butterflies use polarized skylight for migratory orientation?

Abstract: SUMMARY To test if migratory monarch butterflies use polarized light patterns as part of their time-compensated sun compass, we recorded their virtual flight paths in a flight simulator while the butterflies were exposed to patches of naturally polarized blue sky, artificial polarizers or a sunny sky. In addition, we tested butterflies with and without the polarized light detectors of their compound eye being occluded. The monarchs' orientation responses suggested that the butterflies did not us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 25 publications
5
75
0
Order By: Relevance
“…4). This result may appear surprising because vector navigation is the simplest conceivable strategy leading to the least concentrated distribution given the monarchs' known compass orientation capabilities (23,24,26). What we may see here are the effects of additional complicating factors.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…4). This result may appear surprising because vector navigation is the simplest conceivable strategy leading to the least concentrated distribution given the monarchs' known compass orientation capabilities (23,24,26). What we may see here are the effects of additional complicating factors.…”
Section: Discussionmentioning
confidence: 85%
“…Both vector navigation (21) and true navigation (22) have been suggested as strategies used by monarchs to find their overwintering sites. To examine these competing hypotheses, we displaced monarchs from Ontario to Alberta provinces in Canada during fall migration and used flight simulators (23,24) to track their migratory direction. We also used over 5 decades of tagging-recovery data to estimate the directional concentration of monarch butterflies during fall migration, and then compared these results with two mathematical models describing the directional distribution of migrants expected under a simple vector-navigation strategy (16,25).…”
Section: Monarch Butterflies (Danaus Plexippus) Breeding In Eastern Nmentioning
confidence: 99%
“…This agrees with conclusions drawn from other experiments (Byrne et al, 2003;Dacke et al, 2014) and further supports the idea that the sun is the most important cue for the orientation system of diurnal dung beetles. This conclusion also holds true for monarch butterflies (Reppert et al, 2004), where polarized skylight seems to play only a minor role as a compass cue (Stalleicken et al, 2005). In contrast to this, ants and crepuscular beetles, primarily, rely on polarized light for orientation (Dacke et al, 2004;Wehner and Müller, 2006).…”
Section: The Hierarchy Of Compass Cuesmentioning
confidence: 80%
“…Ultraviolet pattern elements in butterflies are often structural in nature and therefore might also be polarized (Silberglied, 1984;Kemp et al, 2005). Furthermore, recent work on the nymphalid butterfly Danaus plexippus has shown that the dorsal rim area of their compound eyes is sensitive to ultraviolet polarized light and that this may function in skylight orientation (Sauman et al, 2005;Stalleicken et al, 2005). Due to limitations inherent in the methods of this study, the potential importance of ultraviolet polarized patterns on butterfly wings could not be assessed.…”
Section: Survey and False-color Photographymentioning
confidence: 94%